n*(-2)=-11

Simple and best practice solution for n*(-2)=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n*(-2)=-11 equation:


Simplifying
n(-2) = -11

Reorder the terms for easier multiplication:
-2n = -11

Solving
-2n = -11

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Divide each side by '-2'.
n = 5.5

Simplifying
n = 5.5

See similar equations:

| -4x-4=0 | | 1+.6(q-4)=.4(q+1) | | 0.7x-4.7=0.9 | | 5m+2(mh)=23 | | 7-2r=15 | | 2x-7+3x=53 | | 3x+4x=x+6 | | .40x+.20(130)=.20(128) | | 7k-2=12 | | -3c-12=-5c+c | | 9J+3= | | 7y+3(y-6)=5(y+1)-2 | | 2x+5x=3x | | 4(6-3x)-8(X-24)=-7X+X | | 33+15x=3x-x+4x | | 17+5y+9=3y+5y+9 | | 6x-15+2x=7 | | X-4=x+1 | | 4x+5=2x-15 | | -5t+10=8t-9 | | 4z+2-z=9+2z+9 | | 7.6-5x+5.5=1.6 | | 10+4x+6x=-1 | | -7x-2=40 | | 2b-3=18 | | 3(5-a)-23=21a-4(2+6a) | | X+28=49 | | 4(x-5)=3(x-2) | | 2c+25=100 | | 2.32x+7.41=-4.78x-8.21 | | -44=6x+7x+8 | | 6-(2p+5)=6[(2p-5)-(p-3)] |

Equations solver categories